2019
DOI: 10.1101/850586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expanded huntingtin CAG repeats disrupt the balance between neural progenitor expansion and differentiation in human cerebral organoids

Abstract: Huntington disease (HD) manifests in both adult and juvenile forms. Mutant HTT gene carriers are thought to undergo normal brain development followed by a degenerative phase, resulting in progressive clinical manifestations. However, recent studies in children and prodromal individuals at risk for HD have raised the possibility of abnormal neurodevelopment.Although key findings in rodent models support this notion, direct evidence in the context of human physiology remains lacking. Using a panel of isogenic HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…The critical role for HTT in the brain has also led to the suggestion that HD is a neurodevelopmental disorder, rather than simply an adult neurodegenerative disorder (Wiatr et al 2018) and has also led to the assumption that mHTT carriers experience normal brain development, but that an emerging degenerative phase ultimately leads to the appearance of clinical symptoms. A recent study based on human organoids suggests that the CAG/glutamine repeat length in HTT regulates neurogenesis during early development (Zhang et al 2019), while a repeat length below the disease threshold benefits brain structure and general intelligence among children aged 6-18 years of age (Lee et al 2017). These same authors also reported that a higher repeat length (as long as it is below disease threshold) gives females an advantage on cortical thickness and intelligence.…”
Section: Discussionmentioning
confidence: 93%
“…The critical role for HTT in the brain has also led to the suggestion that HD is a neurodevelopmental disorder, rather than simply an adult neurodegenerative disorder (Wiatr et al 2018) and has also led to the assumption that mHTT carriers experience normal brain development, but that an emerging degenerative phase ultimately leads to the appearance of clinical symptoms. A recent study based on human organoids suggests that the CAG/glutamine repeat length in HTT regulates neurogenesis during early development (Zhang et al 2019), while a repeat length below the disease threshold benefits brain structure and general intelligence among children aged 6-18 years of age (Lee et al 2017). These same authors also reported that a higher repeat length (as long as it is below disease threshold) gives females an advantage on cortical thickness and intelligence.…”
Section: Discussionmentioning
confidence: 93%
“…A similar hypothesis that mHTT may cause early defect during neurodevelopment and neurogenesis led the research team of Zhang et al [52] to study mention impact of mHTT and CAG repeat length using isogenic HD human ESC/HD iPSC-derived brain organoids. Obtained results from organoids examination showed a lower number of neuroepithelial structures, reduced size, and abnormal development of large radial structures together with the disorganization of neural progenitors.…”
Section: Ipsc-derived Brain Organoid Modelsmentioning
confidence: 94%
“…The dysfunction of NSCs/NPCs under conditions of HD pathology, including both juvenile- and adult-onset, is illustrated. Juvenile-onset HD, in which mutant HTT (mHTT) contains over 60 CAG repeats, is characterized by a decrease in the differentiation of NSCs/NPCs in different in vitro models, with the exception of data that were published by Zhang et al (2019) who discovered premature neurogenesis and neuronal differentiation (the reference is indicated in the figure by an up arrow). Furthermore, NSCs/NPCs exhibited decreases in neurogenesis and disruption in cell organization in juvenile-onset HD.…”
Section: Dysregulation Of Soce In Ipsc-derived Models From Hd Patientmentioning
confidence: 99%
“…All illustrated HD organoids, including two region-specific brain organoids that consist of the three-dimensional (3D) human striatal spheroid (hStrS) and human cortical spheroid (hCS) that were used to create the assembloid by Miura et al (2020) , originated from induced pluripotent stem cells (iPSCs). Cortical organoids ( Conforti et al, 2018 ; Zhang et al, 2019 ) and the chimeric organoids ( Zhang et al, 2019 ) represent 3D cell models of Huntington’s disease. Motor nerve organoids extended axons as a result of their culture in the special chamber with microchannels ( Kawada et al, 2017 ).…”
Section: Modeling Hd Using Brain Organoidsmentioning
confidence: 99%